AB0521 A single-arm, open-label study of the safety and effectiveness of tocilizumab in combination with methotrexate, in patients with rheumatoid arthritis in latin america – preliminary effectiveness results-ritmo study. (23rd January 2014) - Zerbini, C.; Orozco, J.; Martinez, M.; Jaller, J.; Quinteros, A.; Finol, Y.; Facal, J.; Villacís, R.; Alfaro, J.; Faustino, P.; Sáenz, R.
Abstract : Objectives: To present the preliminary effectiveness data of TCZ + MTX treatment, with regard to reduction in signs and symptoms over 6 months in Latin American pts with mod/severe RA, MTX-IR. Methods: Ritmo is a single-arm, open-label, prospective study, performed at 69 sites (18 Brazil, 12 Colombia, 9 Chile, 7 Mexico, 6 Argentina, 5 Ecuador, 4 Peru, 4 Costa Rica, 3 Venezuela, 1 Uruguay). Pts received TCZ 8 mg/kg IV/4wks + MTX(10-25mg/wk). Endpoints at wk24 included proportion of pts with ACR20/50/70 and DAS28 <2.6, change in DAS28, EULAR resp. and HAQ. Clinical instructions (e.g.AES handling) were similar to the ones in Phase III trials. Results: 362 patients were included (ITT). Mean age was 51 yrs, 88% women, with mean disease duration of 11yrs. RF positive in 79% of pts. Mean±SD Baseline DAS28 was 6.45±1.0 and mean±SD HAQ-DI score 1.55±0.7. 319 pts (88%) completed the 24wk treatment. At wk24, 63% of pts (95% CI: [57.9; 68, 3]) had achieved the primary objective (ACR50). ACR20/70 rates were 72.6% (95% CI: [67.6; 77.2]) and 20.8% (95% CI: [16.7; 25.5]), respectively. DAS28 <2.6 was achieved by 54.4% of pts. Mean±SD change in DAS28 score was 3.9±1.43 (p<0.0001). Good and moderate EULAR responses were observed in 73.3% and 24.3% of pts, respectively. Mean±SD change in HAQ-DI was 0.92±0.7 (p<0.0001). TCZ safety profile was comparable to that previously observed. Figure 1: ACR 20/50/70 responses over 24 weeks. Conclusions: At wk24, significant improvement was observed and the safety profile of TCZ was comparable to that previously observed. These results suggest that TCZ is a therapeutic option in our region as suggested by data from the Pivotal Trials in DMARD-IR population. 1-3 References: Smolen J, et al. Lancet 2008; 371:987-97. Genovese M, et al. Arthritis Rheum 2008; 58:2968-80. Kremer et al. Arthritis Rheum 2011;63(3):609-21. Disclosure of Interest: C. Zerbini Grant/Research support from: Roche, Jansen, Pfizer, Sanofi-Aventis, J. Orozco Grant/Research support from: Roche, M. Martinez Grant/Research support from: Roche, J. Jaller Grant/Research support from: Roche, A. Quinteros Grant/Research support from: Roche, Y. Finol: None Declared, J. Facal: None Declared, R. Villacís: None Declared, J. Alfaro: None Declared, P. Faustino Employee of: Roche, R. Sáenz: None Declared